2002
DOI: 10.1128/mcb.22.24.8571-8579.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of NF-κB-Mediated Inhibition of c-Jun N-Terminal Kinase Activation Contributes to Tumor Necrosis Factor Alpha-Induced Apoptosis

Abstract: The proinflammatory cytokine tumor necrosis factor alpha (TNF-α) regulates immune responses, inflammation, and programmed cell death (apoptosis). TNF-α exerts its biological activities by activating multiple signaling pathways, including IκB kinase (IKK), c-Jun N-terminal protein kinase (JNK), and caspases. IKK activation inhibits apoptosis through the transcription factor NF-κB, whose target genes include those that encode inhibitors of both caspases and JNK. Despite activation of the antiapoptotic IKK/NF-κB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 64 publications
7
136
0
1
Order By: Relevance
“…These results contrast with some previous reports of NSAID-induced growth inhibition and apoptosis in breast and endometrial cancer cells (Noguchi et al, 1995;Planchon et al, 1995;Han et al, 1998;Arango et al, 2001), but these differences are reconciled by considering that these studies used NSAIDs other than aspirin (Noguchi et al, 1995;Planchon et al, 1995;Han et al, 1998), while others only observed apoptosis after long exposures (48 -96 h) to high concentrations of salicylate out with the therapeutic range (Sotiriou et al, 1999;Arango et al, 2001). The non-CRC cell lines are susceptible to other apoptosis-inducing agents and NFkB activators such as staurosporine and TNFa, respectively, indicating that these cell lines are not generally resistant to apoptosis or NFkB modulation (Mooney et al, 2002;Tang et al, 2002). The observation that aspirin decreased cell viability in one of the three breast cancer cell lines (T47D) is in keeping with epidemiological data that suggest a lesser protective effect of NSAIDs against breast cancer.…”
Section: Discussionsupporting
confidence: 77%
“…These results contrast with some previous reports of NSAID-induced growth inhibition and apoptosis in breast and endometrial cancer cells (Noguchi et al, 1995;Planchon et al, 1995;Han et al, 1998;Arango et al, 2001), but these differences are reconciled by considering that these studies used NSAIDs other than aspirin (Noguchi et al, 1995;Planchon et al, 1995;Han et al, 1998), while others only observed apoptosis after long exposures (48 -96 h) to high concentrations of salicylate out with the therapeutic range (Sotiriou et al, 1999;Arango et al, 2001). The non-CRC cell lines are susceptible to other apoptosis-inducing agents and NFkB activators such as staurosporine and TNFa, respectively, indicating that these cell lines are not generally resistant to apoptosis or NFkB modulation (Mooney et al, 2002;Tang et al, 2002). The observation that aspirin decreased cell viability in one of the three breast cancer cell lines (T47D) is in keeping with epidemiological data that suggest a lesser protective effect of NSAIDs against breast cancer.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have shown that a persistent activation of JNK, which can be attained by inhibiting NF-kB activity, leads to cell death (De Smaele et al, 2001;Javelaud and Besancon, 2001;Tang et al, 2001Tang et al, , 2002. In contrast, transient JNK activation coupled with NF-kB activation leads to an antiapoptotic response through overexpression of the antiapoptotic cIAP-2 protein (Lamb et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…If indeed, TRAIL activated MKK7 and etoposide activated MKK4, the combination would activate JNK better than each alone and perhaps lead to apoptotic synergy. In addition, an increased duration of JNK signaling may be important for JNK-induced apoptosis (32); such an increased duration can result if one stimulus blocks an inhibition, such as by NF-B, to the alternate stimulus (52). Apoptotic synergy could further be explained by actions distal to JNK as, for example, if JNK signals sensitized the mitochondria to respond to TRAIL-induced signals via caspase 8-mediated cleavage of the Bcl-2 homology molecule, BID.…”
Section: Discussionmentioning
confidence: 99%